Structure and Dominance of Secondary Forest Vegetation at the Coal Mine Plan Location, East Kalimantan, Indonesia - Andi Yusuf; Nisrina Putri Hanifah (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study documents vegetation biodiversity in the secondary forest area of the PT Alhasanie coal mining concession, East Kalimantan, Indonesia, as part of the pre-mining environmental baseline survey. Surveys were conducted in 2024 using a systematic nested plot design,